INNV-24. PATIENT SATISFACTION AND COST ANALYSIS OF THE TELEMEDICINE PROGRAM WITHIN A NEURO-ONCOLOGY PROGRAM. (14th November 2022) - Bilenkin, Arkady; Kang, Richard; Prorok, Rachel; Rogers, Andrea; Naso, Cristina; Patel, Krupal; Beer-Furlan, Andre; Liu, James
Abstract: Unique challenges exist in the utilization of telemedicine for neurological and surgical specialties. We examined the differences in patient satisfaction for telemedicine versus in-person Press Ganey survey reports within an integrated Neuro-Oncology Department to assess whether there was a difference between surgical and medical specialties. We also examined the potential cost savings benefits of utilizing telemedicine. 1189 Press Ganey surveys in the Department of Neuro-Oncology (982 in-person and 207 telemedicine) submitted by neurosurgical and neuro-oncology patients between 04/01/2020 and 06/30/2021 were analyzed. Survey results were divided into 4 categories (Access, Provider, Technology (for telemedicine only), and Overall Satisfaction). Results were compared between telemedicine and in-person visits, and by gender, age, insurance, and specialty. Potential time and cost savings were estimated by calculating lost productivity based on census income data with motor vehicle expenses, and round-trip distances with mean visit durations, respectively. The survey results demonstrated that, among telemedicine patients, there were no differences in satisfaction based on gender, age, or insurance. Surgical specialties scored higher in Access, Technology, and Overall. Among in-person patients, patients older than 65 had higher satisfaction for Provider (p=0.0368) and Overall (p=0.0010). Medicare patients returned higher scores compared to non-private insurance for Overall (p=0.0172). Surgical patients scored higher for Access (p=0.0002). When comparing Telemedicine to In-Person scores, In-person satisfaction was higher for Provider for all patients combined. For surgical patients only, Telemedicine scored higher only in Access (p=0.0252). Cost analysis demonstrated that patients saved an average of 155.4 to 175.1 miles and 3.1 to 3.4 hours of travel per visit and average cost savings were 117.84 to 185.00. We conclude that telemedicine lessens the financial and time burden on neuro-oncology patients and yields non-inferior patient-satisfaction when employed in neurosurgery as compared to medicine, despite potential limitations of the technology in neurological and surgical specialties.